2015
DOI: 10.1017/s1751731115000518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of animal mixing as a stressor on biomarkers of autophagy and oxidative stress during pig muscle maturation

Abstract: The objective of this work was to study the postmortem evolution of potential biomarkers of autophagy (Beclin 1, LC3-II/LC3-I ratio) and oxidative stress (total antioxidant activity, TAA; superoxide dismutase activity, SOD and catalase activity, CAT) in the Longissimus dorsi muscle of entire male ((Large White × Landrace) × Duroc) pigs subjected to different management treatments that may promote stress, such as mixing unfamiliar animals at the farm and/or during transport and lairage before slaughter. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
1
20
0
3
Order By: Relevance
“…In addition, the course of infection in different species can be very different. Biomarkers from muscle tissue have also recently been used to detect harmful or stressful situations that may affect animal welfare and meat quality prior to slaughter (Rubio-González et al, 2015). Results reported by this latter study suggested that mixing unfamiliar animals at the farm or at the slaughter house can increase oxidative stress and autophagy in muscle tissue (Rubio-González et al, 2015).…”
Section: Molecular Biomarkers In Pigsmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the course of infection in different species can be very different. Biomarkers from muscle tissue have also recently been used to detect harmful or stressful situations that may affect animal welfare and meat quality prior to slaughter (Rubio-González et al, 2015). Results reported by this latter study suggested that mixing unfamiliar animals at the farm or at the slaughter house can increase oxidative stress and autophagy in muscle tissue (Rubio-González et al, 2015).…”
Section: Molecular Biomarkers In Pigsmentioning
confidence: 81%
“…Biomarkers from muscle tissue have also recently been used to detect harmful or stressful situations that may affect animal welfare and meat quality prior to slaughter (Rubio-González et al, 2015). Results reported by this latter study suggested that mixing unfamiliar animals at the farm or at the slaughter house can increase oxidative stress and autophagy in muscle tissue (Rubio-González et al, 2015). Biomarkers for autophagy include the Beclin1 gene which show an increase in activity under more stressful conditions and could be useful for detecting inappropriate strategies which lead to animal stress and poorer meat quality.…”
Section: Molecular Biomarkers In Pigsmentioning
confidence: 99%
“…It is very likely that pigs from different farms were exposed to different pathogens. Transport in combination with formation of new groups [25] can cause stress for the animals, and can increase the risk of disease occurrence. This first risk factor was associated with the number of supplying farms, and whether the suppliers changed over time.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pigs are social and under some circumstances hierarchical animals [1], hence mixing unfamiliar animals on the same pen produce a stressful situation with physiological consequences on the individuals [26]. Furthermore, there is considerable research interest in human-animal relationship.…”
Section: Introductionmentioning
confidence: 99%